Married to martyrdom: The remarried widow of a Sikh martyr (Punjab, post-1984). (October 2018) - Haripriya, Soibam
The post-1984 situation in Punjab indexes the importance (and fascination) of the symbol of the shahid (martyr) and shahadat (martyrdom) in the Khalistani political project. Through the examination of the narratives of a widowed informant, this article attempts to relate the concept of martyrdom to that of widowhood. The widow Bibi's 'militant' husband was killed in police encounter almost a decade after 1984. Although remarried, Bibi insists on calling herself 'widow' of a 'martyr'. The article examines Bibi's embracing of widowhood as a celebration of identity that is articulated using the trope of martyrdom. I explore the idea of the 'widow of the martyr' and the 'sibling-like' non-conjugal relationship that she shares with her present husband as a way of memorialisation that moves from material/ concrete memorials to narratives as memorials.